A Theoretical Model: Elastic Analysis of the Evolution of the Crypt Opening Between the Fundic Gland and the Pyloric Gland - Xiong, Fei; Liu, Xiao Gang (Frontiers in Physiology, 2018)
In recent years, the microstructure of the gastric mucosa surface has been widely studied with the development of magnified endoscopic technology. However, it is unclear why the crypt opening shape of the fundic gland is different from that ofthe pyloric gland. We attempted to explain the problem by means of physical concepts ,mathematical tools and some pathological perspectives. We can show that the crypt opening shape of the pyloric gland is derived mathematically from that of the fundic gland. Our model suggests that the evolution of the fundic gland and the pyloric gland trigger epithelial-mesenchymal transition.